2023
DOI: 10.7717/peerj.15495
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam versus propofol for procedural sedation: a meta-analysis of randomized controlled trials

Abstract: Background To improve patient tolerability and satisfaction as well as minimize complications, procedural sedation has been widely used. Propofol is the most widely used agent for induction of anesthesia and sedation by anesthesiologists. With a different mechanism compared to propofol, remimazolam is a new short-acting GABA-A receptor agonist. It is an ester-based benzodiazepine. This meta-analysis aims to clarify the efficacy and safety of remimazolam versus propofol for procedure sedation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Hypoxemia and hypotension during procedural sedation are not unusual adverse events [ 31 ]. Older patients are more sensitive to sedatives because of their slower metabolism, lower physiological reserve, and smaller volume of distribution [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxemia and hypotension during procedural sedation are not unusual adverse events [ 31 ]. Older patients are more sensitive to sedatives because of their slower metabolism, lower physiological reserve, and smaller volume of distribution [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension was more common in those who received propofol [28]. A meta-analysis of randomized controlled trials comparing propofol to remimazolam for procedural sedation demonstrated less bradycardia, hypotension and respiratory depression with remimazolam but with a similar efficacy and side effect profile (nausea, vomiting, dizziness) [29]. The induction and recovery time comparing propofol and remimazolam (when reversed with flumazenil) for ambulatory procedures has been shown to be comparable [30].…”
Section: Discussionmentioning
confidence: 99%
“…As a traditional intravenous anesthetic, propofol is characterized by its fast onset and short duration. However, it is associated with adverse reactions, including post-waking dizziness, respiratory and circulatory depression, injection pain, accumulation with prolonged infusion, and metabolic acidosis [ 7 , 8 ]. Patients with liver tumors often have varying degrees of cirrhosis, and structural changes in the liver significantly reduce blood flow, which in turn affects propofol metabolism, thereby increasing the risk of hypotension [ 9 ].…”
Section: Introductionmentioning
confidence: 99%